The Formation of A Muslim Intellectual Community In Indonesia: The Case of Insists - Syukur, Yanuardi (Al-madinah: Journal of Islamic Civilization, 2025)
This paper discusses the formation process of the Indonesian Muslim intellectual community, INSISTS (Institute for the Study of Islamic Thought and Civilizations). The emergence of INSISTS cannot be separated from the broader socio-political and intellectual context in post-Reformation Indonesia, a period marked by the opening of democratic space, the rise of various Islamic movements, and intense debates over the direction of Islamic thought. The 9/11 tragedy and its global repercussions further intensified concerns about the future of Islam, as liberal narratives—promoted domestically by the Liberal Islamic Network (Jaringan Islam Liberal, JIL), gained prominence in Indonesia’s public sphere. Against this backdrop, INSISTS was formed as a response to liberal thinking, seeking to offer an alternative intellectual framework rooted in Islamic tradition. Unlike previous studies on INSISTS that focused primarily on Islamic thought, this study examines INSISTS through the lens of anthropological studies of friendship in the making of Muslim intellectual communities. It highlights that the formation of the INSISTS community is inseparable from the common interests of its actors, particularly the struggle for the Islamization of science. This struggle is carried out by INSISTS actors through continuous intellectual and social activities that reinforce solidarity, networks of friendship, and a shared vision of resisting liberal Islamic influences.